Reconceptualizing Dakwah Organizational Governance: A Transformative Review of Qur’anic Leadership and Delegation - mohammad Fahmy Bin Rapaee; Hamidullah Mahmud (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2025)
Contemporary dakwah organizations face increasing managerial challenges due to social complexity, organizational expansion, and the pressures of modernization. Many institutions struggle to translate Qur’anic values into professional, adaptive, and accountable governance systems, particularly in the areas of delegation, leadership, and organizational structure. This study aims to systematically examine how Qur’anic verses related to delegation, leadership, and organizational structure can be conceptually integrated to address contemporary managerial challenges in dakwah organizations. A Systematic Literature Review (SLR) was conducted following the PRISMA protocol. A total of 42 peer-reviewed articles indexed in Scopus and Web of Science were identified, screened, and analyzed. The data were synthesized using a thematic analysis approach to identify dominant conceptual patterns and theoretical linkages. The findings reveal three interrelated themes. First, Qur’anic delegation embodies strong ethical and structural dimensions that provide a normative foundation for accountable distribution of responsibilities. Second, Qur’anic leadership functions as both a moral compass and a strategic framework for building visionary, trustworthy, and participatory organizations. Third, effective dakwah organizational structures require the integration of Qur’anic values with contemporary management principles to ensure adaptability, sustainability, and institutional resilience. This study offers practical implications for dakwah institutions by providing a conceptual framework that supports professional governance, leadership regeneration, and structural clarity. The findings also inform policymakers and Islamic organizations in designing leadership development programs and organizational reforms grounded in Qur’anic principles. Unlike prior studies that focus primarily on normative or theoretical discussions, this research advances the literature by systematically integrating thematic Qur’anic analysis with modern organizational and leadership theories through an SLR approach, resulting in a transformative and applicable conceptual model for contemporary dakwah organizations.